استخدام طريقة التحليل الهرمي AHP في تحديد المواقع الملائمة لتوزيع مياه الجفت OMWW - عادل عوض; رائد جعفر; فراس خليل (Tishreen University, 2019)
Olive Mill Wastewater OMWW is a major pollutant that threatens water sources at production sites due to quality and high concentration of pollutants, which are difficult to treat effectively within treatment plants. However, the method used to deal with these pollutants is distribution to agricultural land as fertilizer, according to a set of conditions and criteria. The Analytical Hierarchy Process (AHP) provides us an effective scientific tool that assists and supports the decision making process in determining the most suitable location for applying this method. This paper presents a theoretical review of AHP, and a numerical application of this method in determining the appropriate location for the distribution of OMWW using a single decision maker and based on the eigenvector approach to finding priorities. This paper also presents two additional methods to derive priority values and because most decisions affect the lives of a group of people, we ask a group of experts to evaluate alternatives to make final decision; this paper also presents two methods for aggregating individual judgments. Finally, some conclusions, recommendations and some future trends presented. تعتبر مياه الجفت الناتجة عن صناعة زيت الزيتون من الملوثات السائلة الرئيسية التي تهدد مصادر المياه في أماكن الإنتاج، وذلك بسبب نوعية الملوثات وتراكيزها العالية والتي يصعب معالجتها بصورة فعالة ضمن محطات المعالجة، إلا أن الأسلوب المتبع في إدارة هذه الملوثات هو توزيعها على الأراضي الزراعية بطريقة الري التسميدي، وفقاً لمجموعة من الشروط والمعايير، وتأتي طريقة التحليل الهرمي AHP لتقدم لنا أداة علمية فعالة تساعد وتدعم عملية اتخاذ القرار في تحديد المواقع الأكثر ملائمة لتطبيق هذه الطريقة. هذه الورقة تقدم مراجعة نظرية لطريقة التحليل الهرمي وتطبيق عملي لهذه الطريقة في تحديد المواقع الملائمة لتوزيع مياه الجفت بالاستعانة بصانع قرار وحيد وبالاستناد لطريقة المتجه الذاتي لتحديد الأولويات، وتعرض هذه الورقة أيضاً طريقتين إضافيتين لاشتقاق قيم الأولوية، وكون أغلب القرارات تؤثر في حياة مجموعة من الأشخاص يتم اللجوء إلى مجموعة من الخبراء لتقييم البدائل وصناعة القرار النهائي، هذه الورقة تعرض أيضاً طريقتين لتجميع الأحكام الفردية. وفي النهاية تم عرض بعض الاستنتاجات والتوصيات وبعض الاتجاهات المستقبلية للبحث.